def test_combsimp(): k, m, n = symbols('k m n', integer=True) assert combsimp(factorial(n)) == factorial(n) assert combsimp(binomial(n, k)) == binomial(n, k) assert combsimp(factorial(n) / factorial(n - 3)) == n * (-1 + n) * (-2 + n) assert combsimp(binomial(n + 1, k + 1) / binomial(n, k)) == (1 + n) / (1 + k) assert combsimp(binomial(3*n + 4, n + 1)/binomial(3*n + 1, n)) == \ Rational(3, 2)*((3*n + 2)*(3*n + 4)/((n + 1)*(2*n + 3))) assert combsimp(factorial(n)**2/factorial(n - 3)) == \ factorial(n)*n*(-1 + n)*(-2 + n) assert combsimp(factorial(n)*binomial(n + 1, k + 1)/binomial(n, k)) == \ factorial(n + 1)/(1 + k) assert combsimp(gamma(n + 3)) == factorial(n + 2) assert combsimp(factorial(x)) == gamma(x + 1) # issue 9699 assert combsimp((n + 1) * factorial(n)) == factorial(n + 1) assert combsimp(factorial(n) / n) == factorial(n - 1) # issue 6658 assert combsimp(binomial(n, n - k)) == binomial(n, k) # issue 6341, 7135 assert combsimp(factorial(n)/(factorial(k)*factorial(n - k))) == \ binomial(n, k) assert combsimp(factorial(k)*factorial(n - k)/factorial(n)) == \ 1/binomial(n, k) assert combsimp(factorial(2 * n) / factorial(n)**2) == binomial(2 * n, n) assert combsimp( factorial(2 * n) * factorial(k) * factorial(n - k) / factorial(n)**3) == binomial(2 * n, n) / binomial(n, k) assert combsimp(factorial(n * (1 + n) - n**2 - n)) == 1 assert combsimp(6*FallingFactorial(-4, n)/factorial(n)) == \ (-1)**n*(n + 1)*(n + 2)*(n + 3) assert combsimp(6*FallingFactorial(-4, n - 1)/factorial(n - 1)) == \ (-1)**(n - 1)*n*(n + 1)*(n + 2) assert combsimp(6*FallingFactorial(-4, n - 3)/factorial(n - 3)) == \ (-1)**(n - 3)*n*(n - 1)*(n - 2) assert combsimp(6*FallingFactorial(-4, -n - 1)/factorial(-n - 1)) == \ -(-1)**(-n - 1)*n*(n - 1)*(n - 2) assert combsimp(6*RisingFactorial(4, n)/factorial(n)) == \ (n + 1)*(n + 2)*(n + 3) assert combsimp(6*RisingFactorial(4, n - 1)/factorial(n - 1)) == \ n*(n + 1)*(n + 2) assert combsimp(6*RisingFactorial(4, n - 3)/factorial(n - 3)) == \ n*(n - 1)*(n - 2) assert combsimp(6*RisingFactorial(4, -n - 1)/factorial(-n - 1)) == \ -n*(n - 1)*(n - 2)
def test_combsimp(): from sympy.abc import n, k assert combsimp(factorial(n)) == factorial(n) assert combsimp(binomial(n, k)) == binomial(n, k) assert combsimp(factorial(n) / factorial(n - 3)) == n * (-1 + n) * (-2 + n) assert combsimp(binomial(n + 1, k + 1) / binomial(n, k)) == (1 + n) / (1 + k) assert combsimp(binomial(3*n + 4, n + 1)/binomial(3*n + 1, n)) == \ S(3)/2*((3*n + 2)*(3*n + 4)/((n + 1)*(2*n + 3))) assert combsimp(factorial(n)**2/factorial(n - 3)) == \ factorial(n)*n*(-1 + n)*(-2 + n) assert combsimp(factorial(n)*binomial(n + 1, k + 1)/binomial(n, k)) == \ factorial(n + 1)/(1 + k) assert combsimp(binomial(n - 1, k)) == -((-n + k) * binomial(n, k)) / n assert combsimp(binomial(n + 2, k + S(1) / 2)) == 4 * ( (n + 1) * (n + 2) * binomial(n, k + S(1) / 2)) / ((2 * k - 2 * n - 1) * (2 * k - 2 * n - 3)) assert combsimp(binomial(n + 2, k + 2.0)) == \ Mul(-2.0, 0.5*n + 1.0, binomial(n + 1.0, k + 2.0), evaluate = False)/(k - n) # coverage tests assert combsimp(factorial(n * (1 + n) - n**2 - n)) == 1 assert combsimp(binomial(n + k - 2, n)) == \ k*(k - 1)*binomial(n + k, n)/((n + k)*(n + k - 1)) i = Symbol('i', integer=True) e = gamma(i + 3) assert combsimp(e) == e e = gamma(exp(i)) assert combsimp(e) == e e = gamma(n + S(1) / 3) * gamma(n + S(2) / 3) assert combsimp(e) == e assert combsimp(gamma(4*n + S(1)/2)/gamma(2*n - S(3)/4)) == \ 2**(4*n - S(5)/2)*(8*n - 3)*gamma(2*n + S(3)/4)/sqrt(pi) assert combsimp(6*FallingFactorial(-4, n)/factorial(n)) == \ (-1)**n*(n + 1)*(n + 2)*(n + 3) assert combsimp(6*FallingFactorial(-4, n - 1)/factorial(n - 1)) == \ (-1)**(n - 1)*n*(n + 1)*(n + 2) assert combsimp(6*FallingFactorial(-4, n - 3)/factorial(n - 3)) == \ (-1)**(n - 3)*n*(n - 1)*(n - 2) assert combsimp(6*FallingFactorial(-4, -n - 1)/factorial(-n - 1)) == \ -(-1)**(-n - 1)*n*(n - 1)*(n - 2) assert combsimp(6*RisingFactorial(4, n)/factorial(n)) == \ (n + 1)*(n + 2)*(n + 3) assert combsimp(6*RisingFactorial(4, n - 1)/factorial(n - 1)) == \ n*(n + 1)*(n + 2) assert combsimp(6*RisingFactorial(4, n - 3)/factorial(n - 3)) == \ n*(n - 1)*(n - 2) assert combsimp(6*RisingFactorial(4, -n - 1)/factorial(-n - 1)) == \ -n*(n - 1)*(n - 2)
def test_latex_functions(): assert latex(exp(x)) == "e^{x}" assert latex(exp(1) + exp(2)) == "e + e^{2}" f = Function('f') assert latex(f(x)) == '\\operatorname{f}{\\left (x \\right )}' beta = Function('beta') assert latex(beta(x)) == r"\beta{\left (x \right )}" assert latex(sin(x)) == r"\sin{\left (x \right )}" assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}" assert latex(sin(2*x**2), fold_func_brackets=True) == \ r"\sin {2 x^{2}}" assert latex(sin(x**2), fold_func_brackets=True) == \ r"\sin {x^{2}}" assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}" assert latex(asin(x)**2,inv_trig_style="full") == \ r"\arcsin^{2}{\left (x \right )}" assert latex(asin(x)**2,inv_trig_style="power") == \ r"\sin^{-1}{\left (x \right )}^{2}" assert latex(asin(x**2),inv_trig_style="power",fold_func_brackets=True) == \ r"\sin^{-1} {x^{2}}" assert latex(factorial(k)) == r"k!" assert latex(factorial(-k)) == r"\left(- k\right)!" assert latex(factorial2(k)) == r"k!!" assert latex(factorial2(-k)) == r"\left(- k\right)!!" assert latex(binomial(2, k)) == r"{\binom{2}{k}}" assert latex(FallingFactorial(3, k)) == r"{\left(3\right)}_{\left(k\right)}" assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}" assert latex(floor(x)) == r"\lfloor{x}\rfloor" assert latex(ceiling(x)) == r"\lceil{x}\rceil" assert latex(Abs(x)) == r"\lvert{x}\rvert" assert latex(re(x)) == r"\Re{x}" assert latex(re(x + y)) == r"\Re {\left (x + y \right )}" assert latex(im(x)) == r"\Im{x}" assert latex(conjugate(x)) == r"\overline{x}" assert latex(gamma(x)) == r"\Gamma\left(x\right)" assert latex(Order(x)) == r"\mathcal{O}\left(x\right)" assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)' assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)' assert latex(cot(x)) == r'\cot{\left (x \right )}' assert latex(coth(x)) == r'\coth{\left (x \right )}' assert latex(re(x)) == r'\Re{x}' assert latex(im(x)) == r'\Im{x}' assert latex(root(x, y)) == r'x^{\frac{1}{y}}' assert latex(arg(x)) == r'\arg{\left (x \right )}' assert latex(zeta(x)) == r'\zeta{\left (x \right )}'
def test_factorial_moment(): X = Poisson('X', 2) Y = Binomial('Y', 2, S.Half) Z = Hypergeometric('Z', 4, 2, 2) assert factorial_moment(X, 2) == 4 assert factorial_moment(Y, 2) == S.Half assert factorial_moment(Z, 2) == Rational(1, 3) x, y, z, l = symbols('x y z l') Y = Binomial('Y', 2, y) Z = Hypergeometric('Z', 10, 2, 3) assert factorial_moment(Y, l) == y**2*FallingFactorial( 2, l) + 2*y*(1 - y)*FallingFactorial(1, l) + (1 - y)**2*\ FallingFactorial(0, l) assert factorial_moment(Z, l) == 7*FallingFactorial(0, l)/\ 15 + 7*FallingFactorial(1, l)/15 + FallingFactorial(2, l)/15
def factorial_moment(X, n, condition=None, **kwargs): """ The factorial moment is a mathematical quantity defined as the expectation or average of the falling factorial of a random variable. .. math:: factorial-moment(X, n) = E(X(X - 1)(X - 2)...(X - n + 1)) Parameters ========== n: A natural number, n-th factorial moment. condition : Expr containing RandomSymbols A conditional expression. Examples ======== >>> from sympy.stats import factorial_moment, Poisson, Binomial >>> from sympy import Symbol, S >>> lamda = Symbol('lamda') >>> X = Poisson('X', lamda) >>> factorial_moment(X, 2) lamda**2 >>> Y = Binomial('Y', 2, S.Half) >>> factorial_moment(Y, 2) 1/2 >>> factorial_moment(Y, 2, Y > 1) # find factorial moment for Y > 1 2 References ========== .. [1] https://en.wikipedia.org/wiki/Factorial_moment .. [2] http://mathworld.wolfram.com/FactorialMoment.html """ return expectation(FallingFactorial(X, n), condition=condition, **kwargs)
def test_factorial_moment(): X = Poisson("X", 2) Y = Binomial("Y", 2, S.Half) Z = Hypergeometric("Z", 4, 2, 2) assert factorial_moment(X, 2) == 4 assert factorial_moment(Y, 2) == S.Half assert factorial_moment(Z, 2) == Rational(1, 3) x, y, z, l = symbols("x y z l") Y = Binomial("Y", 2, y) Z = Hypergeometric("Z", 10, 2, 3) assert factorial_moment(Y, l) == y ** 2 * FallingFactorial(2, l) + 2 * y * ( 1 - y ) * FallingFactorial(1, l) + (1 - y) ** 2 * FallingFactorial(0, l) assert ( factorial_moment(Z, l) == 7 * FallingFactorial(0, l) / 15 + 7 * FallingFactorial(1, l) / 15 + FallingFactorial(2, l) / 15 )
def test_latex_functions(): assert latex(exp(x)) == "e^{x}" assert latex(exp(1) + exp(2)) == "e + e^{2}" f = Function('f') assert latex(f(x)) == '\\operatorname{f}{\\left (x \\right )}' beta = Function('beta') assert latex(beta(x)) == r"\beta{\left (x \right )}" assert latex(sin(x)) == r"\sin{\left (x \right )}" assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}" assert latex(sin(2*x**2), fold_func_brackets=True) == \ r"\sin {2 x^{2}}" assert latex(sin(x**2), fold_func_brackets=True) == \ r"\sin {x^{2}}" assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}" assert latex(asin(x)**2, inv_trig_style="full") == \ r"\arcsin^{2}{\left (x \right )}" assert latex(asin(x)**2, inv_trig_style="power") == \ r"\sin^{-1}{\left (x \right )}^{2}" assert latex(asin(x**2), inv_trig_style="power", fold_func_brackets=True) == \ r"\sin^{-1} {x^{2}}" assert latex(factorial(k)) == r"k!" assert latex(factorial(-k)) == r"\left(- k\right)!" assert latex(subfactorial(k)) == r"!k" assert latex(subfactorial(-k)) == r"!\left(- k\right)" assert latex(factorial2(k)) == r"k!!" assert latex(factorial2(-k)) == r"\left(- k\right)!!" assert latex(binomial(2, k)) == r"{\binom{2}{k}}" assert latex(FallingFactorial(3, k)) == r"{\left(3\right)}_{\left(k\right)}" assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}" assert latex(floor(x)) == r"\lfloor{x}\rfloor" assert latex(ceiling(x)) == r"\lceil{x}\rceil" assert latex(Min(x, 2, x**3)) == r"\min\left(2, x, x^{3}\right)" assert latex(Min(x, y)**2) == r"\min\left(x, y\right)^{2}" assert latex(Max(x, 2, x**3)) == r"\max\left(2, x, x^{3}\right)" assert latex(Max(x, y)**2) == r"\max\left(x, y\right)^{2}" assert latex(Abs(x)) == r"\lvert{x}\rvert" assert latex(re(x)) == r"\Re{x}" assert latex(re(x + y)) == r"\Re{x} + \Re{y}" assert latex(im(x)) == r"\Im{x}" assert latex(conjugate(x)) == r"\overline{x}" assert latex(gamma(x)) == r"\Gamma\left(x\right)" assert latex(Order(x)) == r"\mathcal{O}\left(x\right)" assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)' assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)' assert latex(cot(x)) == r'\cot{\left (x \right )}' assert latex(coth(x)) == r'\coth{\left (x \right )}' assert latex(re(x)) == r'\Re{x}' assert latex(im(x)) == r'\Im{x}' assert latex(root(x, y)) == r'x^{\frac{1}{y}}' assert latex(arg(x)) == r'\arg{\left (x \right )}' assert latex(zeta(x)) == r'\zeta\left(x\right)' assert latex(zeta(x)) == r"\zeta\left(x\right)" assert latex(zeta(x)**2) == r"\zeta^{2}\left(x\right)" assert latex(zeta(x, y)) == r"\zeta\left(x, y\right)" assert latex(zeta(x, y)**2) == r"\zeta^{2}\left(x, y\right)" assert latex(dirichlet_eta(x)) == r"\eta\left(x\right)" assert latex(dirichlet_eta(x)**2) == r"\eta^{2}\left(x\right)" assert latex(polylog(x, y)) == r"\operatorname{Li}_{x}\left(y\right)" assert latex(polylog(x, y)**2) == r"\operatorname{Li}_{x}^{2}\left(y\right)" assert latex(lerchphi(x, y, n)) == r"\Phi\left(x, y, n\right)" assert latex(lerchphi(x, y, n)**2) == r"\Phi^{2}\left(x, y, n\right)" assert latex(Ei(x)) == r'\operatorname{Ei}{\left (x \right )}' assert latex(Ei(x)**2) == r'\operatorname{Ei}^{2}{\left (x \right )}' assert latex(expint(x, y)**2) == r'\operatorname{E}_{x}^{2}\left(y\right)' assert latex(Shi(x)**2) == r'\operatorname{Shi}^{2}{\left (x \right )}' assert latex(Si(x)**2) == r'\operatorname{Si}^{2}{\left (x \right )}' assert latex(Ci(x)**2) == r'\operatorname{Ci}^{2}{\left (x \right )}' assert latex(Chi(x)**2) == r'\operatorname{Chi}^{2}{\left (x \right )}' assert latex(jacobi(n, a, b, x)) == r'P_{n}^{\left(a,b\right)}\left(x\right)' assert latex(jacobi( n, a, b, x)**2) == r'\left(P_{n}^{\left(a,b\right)}\left(x\right)\right)^{2}' assert latex(gegenbauer(n, a, x)) == r'C_{n}^{\left(a\right)}\left(x\right)' assert latex(gegenbauer( n, a, x)**2) == r'\left(C_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(chebyshevt(n, x)) == r'T_{n}\left(x\right)' assert latex(chebyshevt(n, x)**2) == r'\left(T_{n}\left(x\right)\right)^{2}' assert latex(chebyshevu(n, x)) == r'U_{n}\left(x\right)' assert latex(chebyshevu(n, x)**2) == r'\left(U_{n}\left(x\right)\right)^{2}' assert latex(legendre(n, x)) == r'P_{n}\left(x\right)' assert latex(legendre(n, x)**2) == r'\left(P_{n}\left(x\right)\right)^{2}' assert latex(assoc_legendre(n, a, x)) == r'P_{n}^{\left(a\right)}\left(x\right)' assert latex(assoc_legendre( n, a, x)**2) == r'\left(P_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(laguerre(n, x)) == r'L_{n}\left(x\right)' assert latex(laguerre(n, x)**2) == r'\left(L_{n}\left(x\right)\right)^{2}' assert latex(assoc_laguerre(n, a, x)) == r'L_{n}^{\left(a\right)}\left(x\right)' assert latex(assoc_laguerre( n, a, x)**2) == r'\left(L_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(hermite(n, x)) == r'H_{n}\left(x\right)' assert latex(hermite(n, x)**2) == r'\left(H_{n}\left(x\right)\right)^{2}' # Test latex printing of function names with "_" assert latex( polar_lift(0)) == r"\operatorname{polar\_lift}{\left (0 \right )}" assert latex(polar_lift(0)** 3) == r"\operatorname{polar\_lift}^{3}{\left (0 \right )}"
def test_latex_functions(): assert latex(exp(x)) == "e^{x}" assert latex(exp(1) + exp(2)) == "e + e^{2}" f = Function('f') assert latex(f(x)) == r'f{\left (x \right )}' assert latex(f) == r'f' g = Function('g') assert latex(g(x, y)) == r'g{\left (x,y \right )}' assert latex(g) == r'g' h = Function('h') assert latex(h(x, y, z)) == r'h{\left (x,y,z \right )}' assert latex(h) == r'h' Li = Function('Li') assert latex(Li) == r'\operatorname{Li}' assert latex(Li(x)) == r'\operatorname{Li}{\left (x \right )}' beta = Function('beta') # not to be confused with the beta function assert latex(beta(x)) == r"\beta{\left (x \right )}" assert latex(beta) == r"\beta" assert latex(sin(x)) == r"\sin{\left (x \right )}" assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}" assert latex(sin(2*x**2), fold_func_brackets=True) == \ r"\sin {2 x^{2}}" assert latex(sin(x**2), fold_func_brackets=True) == \ r"\sin {x^{2}}" assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}" assert latex(asin(x)**2, inv_trig_style="full") == \ r"\arcsin^{2}{\left (x \right )}" assert latex(asin(x)**2, inv_trig_style="power") == \ r"\sin^{-1}{\left (x \right )}^{2}" assert latex(asin(x**2), inv_trig_style="power", fold_func_brackets=True) == \ r"\sin^{-1} {x^{2}}" assert latex(factorial(k)) == r"k!" assert latex(factorial(-k)) == r"\left(- k\right)!" assert latex(subfactorial(k)) == r"!k" assert latex(subfactorial(-k)) == r"!\left(- k\right)" assert latex(factorial2(k)) == r"k!!" assert latex(factorial2(-k)) == r"\left(- k\right)!!" assert latex(binomial(2, k)) == r"{\binom{2}{k}}" assert latex(FallingFactorial(3, k)) == r"{\left(3\right)}_{\left(k\right)}" assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}" assert latex(floor(x)) == r"\lfloor{x}\rfloor" assert latex(ceiling(x)) == r"\lceil{x}\rceil" assert latex(Min(x, 2, x**3)) == r"\min\left(2, x, x^{3}\right)" assert latex(Min(x, y)**2) == r"\min\left(x, y\right)^{2}" assert latex(Max(x, 2, x**3)) == r"\max\left(2, x, x^{3}\right)" assert latex(Max(x, y)**2) == r"\max\left(x, y\right)^{2}" assert latex(Abs(x)) == r"\left\lvert{x}\right\rvert" assert latex(re(x)) == r"\Re{x}" assert latex(re(x + y)) == r"\Re{x} + \Re{y}" assert latex(im(x)) == r"\Im{x}" assert latex(conjugate(x)) == r"\overline{x}" assert latex(gamma(x)) == r"\Gamma{\left(x \right)}" w = Wild('w') assert latex(gamma(w)) == r"\Gamma{\left(w \right)}" assert latex(Order(x)) == r"\mathcal{O}\left(x\right)" assert latex(Order(x, x)) == r"\mathcal{O}\left(x\right)" assert latex(Order(x, x, 0)) == r"\mathcal{O}\left(x\right)" assert latex(Order(x, x, oo)) == r"\mathcal{O}\left(x; x\rightarrow\infty\right)" assert latex( Order(x, x, y) ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow0\right)" assert latex( Order(x, x, y, 0) ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow0\right)" assert latex( Order(x, x, y, oo) ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow\infty\right)" assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)' assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)' assert latex(cot(x)) == r'\cot{\left (x \right )}' assert latex(coth(x)) == r'\coth{\left (x \right )}' assert latex(re(x)) == r'\Re{x}' assert latex(im(x)) == r'\Im{x}' assert latex(root(x, y)) == r'x^{\frac{1}{y}}' assert latex(arg(x)) == r'\arg{\left (x \right )}' assert latex(zeta(x)) == r'\zeta\left(x\right)' assert latex(zeta(x)) == r"\zeta\left(x\right)" assert latex(zeta(x)**2) == r"\zeta^{2}\left(x\right)" assert latex(zeta(x, y)) == r"\zeta\left(x, y\right)" assert latex(zeta(x, y)**2) == r"\zeta^{2}\left(x, y\right)" assert latex(dirichlet_eta(x)) == r"\eta\left(x\right)" assert latex(dirichlet_eta(x)**2) == r"\eta^{2}\left(x\right)" assert latex(polylog(x, y)) == r"\operatorname{Li}_{x}\left(y\right)" assert latex(polylog(x, y)**2) == r"\operatorname{Li}_{x}^{2}\left(y\right)" assert latex(lerchphi(x, y, n)) == r"\Phi\left(x, y, n\right)" assert latex(lerchphi(x, y, n)**2) == r"\Phi^{2}\left(x, y, n\right)" assert latex(elliptic_k(z)) == r"K\left(z\right)" assert latex(elliptic_k(z)**2) == r"K^{2}\left(z\right)" assert latex(elliptic_f(x, y)) == r"F\left(x\middle| y\right)" assert latex(elliptic_f(x, y)**2) == r"F^{2}\left(x\middle| y\right)" assert latex(elliptic_e(x, y)) == r"E\left(x\middle| y\right)" assert latex(elliptic_e(x, y)**2) == r"E^{2}\left(x\middle| y\right)" assert latex(elliptic_e(z)) == r"E\left(z\right)" assert latex(elliptic_e(z)**2) == r"E^{2}\left(z\right)" assert latex(elliptic_pi(x, y, z)) == r"\Pi\left(x; y\middle| z\right)" assert latex(elliptic_pi(x, y, z)**2) == \ r"\Pi^{2}\left(x; y\middle| z\right)" assert latex(elliptic_pi(x, y)) == r"\Pi\left(x\middle| y\right)" assert latex(elliptic_pi(x, y)**2) == r"\Pi^{2}\left(x\middle| y\right)" assert latex(Ei(x)) == r'\operatorname{Ei}{\left (x \right )}' assert latex(Ei(x)**2) == r'\operatorname{Ei}^{2}{\left (x \right )}' assert latex(expint(x, y)**2) == r'\operatorname{E}_{x}^{2}\left(y\right)' assert latex(Shi(x)**2) == r'\operatorname{Shi}^{2}{\left (x \right )}' assert latex(Si(x)**2) == r'\operatorname{Si}^{2}{\left (x \right )}' assert latex(Ci(x)**2) == r'\operatorname{Ci}^{2}{\left (x \right )}' assert latex(Chi(x)**2) == r'\operatorname{Chi}^{2}{\left (x \right )}' assert latex(Chi(x)) == r'\operatorname{Chi}{\left (x \right )}' assert latex(jacobi(n, a, b, x)) == r'P_{n}^{\left(a,b\right)}\left(x\right)' assert latex(jacobi( n, a, b, x)**2) == r'\left(P_{n}^{\left(a,b\right)}\left(x\right)\right)^{2}' assert latex(gegenbauer(n, a, x)) == r'C_{n}^{\left(a\right)}\left(x\right)' assert latex(gegenbauer( n, a, x)**2) == r'\left(C_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(chebyshevt(n, x)) == r'T_{n}\left(x\right)' assert latex(chebyshevt(n, x)**2) == r'\left(T_{n}\left(x\right)\right)^{2}' assert latex(chebyshevu(n, x)) == r'U_{n}\left(x\right)' assert latex(chebyshevu(n, x)**2) == r'\left(U_{n}\left(x\right)\right)^{2}' assert latex(legendre(n, x)) == r'P_{n}\left(x\right)' assert latex(legendre(n, x)**2) == r'\left(P_{n}\left(x\right)\right)^{2}' assert latex(assoc_legendre(n, a, x)) == r'P_{n}^{\left(a\right)}\left(x\right)' assert latex(assoc_legendre( n, a, x)**2) == r'\left(P_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(laguerre(n, x)) == r'L_{n}\left(x\right)' assert latex(laguerre(n, x)**2) == r'\left(L_{n}\left(x\right)\right)^{2}' assert latex(assoc_laguerre(n, a, x)) == r'L_{n}^{\left(a\right)}\left(x\right)' assert latex(assoc_laguerre( n, a, x)**2) == r'\left(L_{n}^{\left(a\right)}\left(x\right)\right)^{2}' assert latex(hermite(n, x)) == r'H_{n}\left(x\right)' assert latex(hermite(n, x)**2) == r'\left(H_{n}\left(x\right)\right)^{2}' theta = Symbol("theta", real=True) phi = Symbol("phi", real=True) assert latex(Ynm(n, m, theta, phi)) == r'Y_{n}^{m}\left(\theta,\phi\right)' assert latex( Ynm(n, m, theta, phi)**3) == r'\left(Y_{n}^{m}\left(\theta,\phi\right)\right)^{3}' assert latex(Znm(n, m, theta, phi)) == r'Z_{n}^{m}\left(\theta,\phi\right)' assert latex( Znm(n, m, theta, phi)**3) == r'\left(Z_{n}^{m}\left(\theta,\phi\right)\right)^{3}' # Test latex printing of function names with "_" assert latex( polar_lift(0)) == r"\operatorname{polar\_lift}{\left (0 \right )}" assert latex(polar_lift(0)** 3) == r"\operatorname{polar\_lift}^{3}{\left (0 \right )}" assert latex(totient(n)) == r'\phi\left( n \right)' # some unknown function name should get rendered with \operatorname fjlkd = Function('fjlkd') assert latex(fjlkd(x)) == r'\operatorname{fjlkd}{\left (x \right )}' # even when it is referred to without an argument assert latex(fjlkd) == r'\operatorname{fjlkd}'